Insights into Enhancing English Pronunciation and Vocabulary through Drilling and Word Repetition Techniques - Ihsani, Pelangi Fadhilah; Nanda, Deri Sis; Susanto, Susanto (Journal of Scientific Insights, 2025)
Effective pronunciation and vocabulary acquisition are essential in English language learning, particularly for non-native speakers. Drilling and word repetition techniques are widely regarded as effective strategies for enhancing linguistic skills. This study examines the implementation and perceived effectiveness of these techniques in improving pronunciation, vocabulary, and comprehension among eleventh-grade students at SMK Swadhipa 1 Natar, Lampung Province, Indonesia. Using a qualitative descriptive approach, data were collected through a structured questionnaire comprising 25 questions, designed to assess students’ confidence, interest, and perceptions of the effectiveness of these methods. Out of 60 students, 29 participated, sharing valuable insights into their experiences and attitudes toward drilling and repetition techniques. The findings reveal that these methods are effective in improving pronunciation, grammatical understanding, and text comprehension. They also boost students’ confidence and interest by offering opportunities for repeated practice and corrective feedback. However, challenges such as pronunciation difficulties and a lack of confidence were reported, highlighting the need for adaptive and supportive teaching practices. This study underscores the importance of integrating repetitive learning approaches into English instruction to foster effective and engaging learning experiences.